MORPHOMETRIC INDICATORS OF THE FACIAL SKELETON IN INDIVIDUALS WITH COMPLETE AND PARTIAL ADENTIA - Norpulot B. Nurov (Central Asian Journal of Medicine, 2023)
In scientific research, dentists focus on individual changes found in the jaw-face area. One of the main methods for assessing indicators in the tooth-jaw system is based on the fact that morphometric indicators determine the compatibility of tooth sizes with the indicators of the tooth-jaw. Therefore, it is advisable to study and identify topographic identities of anatomical derivatives of the jaw-facial area before orthopedic, orthodontic treatment of patients with dental-jaw research using biometric studies [1, 3].